Reconstruction of Classroom Teacher Management in Improving the Quality of Learning - Firdhaus Tri Nugroho; Nurfuadi Nurfuadi (CV. Edujavare Publishing, 2026)
The background of this study is based on the continued dominance of conventional and teacher-oriented classroom management practices, as well as the suboptimal integration between teacher competence, student involvement, and the use of technology in the learning process. This study aims to analyze the reconstruction of classroom teacher management in an effort to improve the quality of learning. This study uses a qualitative approach with a library research type through a review of various relevant literature sources. The results of the study indicate that the reconstruction of classroom management needs to be directed towards a student-centered approach by integrating pedagogical, social, and personality competencies of teachers, strengthening interactions between teachers and students, and increasing engagement and motivation to learn through the use of learning technology. The novelty of this study lies in the development of a reconstructive and integrative classroom management concept by combining aspects of teacher competence, instructional leadership, and technology use within a comprehensive conceptual framework. Thus, the reconstruction of classroom teacher management is expected to be able to create a learning environment that is more adaptive, collaborative, and oriented towards improving the quality of learning in accordance with the demands of the 21st century.